CaMKIIδ Splice Variants in the Healthy and Diseased Heart - Duran, Javier; Nickel, Lennart; Estrada, Manuel; Backs, Johannes; van den Hoogenhof, Maarten M. G. (Frontiers in Cell and Developmental Biology, 2021)
RNA splicing has been recognized in recent years as a pivotal player in heart development and disease. The Ca2+/calmodulin dependent protein kinase II delta (CaMKIIδ) is a multifunctional Ser/Thr kinase family and generates at least 11 different splice variants through alternative splicing. This enzyme, which belongs to the CaMKII family, is the predominant family member in the heart and functions as a messenger towards adaptive or detrimental signaling in cardiomyocytes. Classically, the nuclear CaMKIIδB and cytoplasmic CaMKIIδC splice variants are described as mediators of arrhythmias, contractile function, Ca2+ handling, and gene transcription. Recent findings also put CaMKIIδA and CaMKIIδ9 as cardinal players in the global CaMKII response in the heart. In this review, we discuss and summarize the new insights into CaMKIIδ splice variants and their (proposed) functions, as well as CaMKII-engineered mouse phenotypes and cardiac dysfunction related to CaMKIIδ missplicing. We also discuss RNA splicing factors affecting CaMKII splicing. Finally, we discuss the translational perspective derived from these insights and future directions on CaMKIIδ splicing research in the healthy and diseased heart.